O ensino de rítmica na banda municipal de Itirapina - SP: relato de experiência - Soares, Woelington Eduardo (Universidade Federal de São Carlos, 2021)
This Experience Report aims to present the process of involvement, assessment and decision-making, in a series of four classes, which address the practice of rhythmic reading, under the reference of names such as Émile Jacques-Dalcroze, Carl Orff and Lucas Ciavatta, who used similar teaching standards in the issue of identification and rhythmic production through the body, being an inspiration for the search for activities that adhere to the methods of these authors. These authors produced works that were decisive for the development of this report, considering that I tried to bring to my classes elements taken from books and articles, as well as works produced by other people who quoted them and interpreted their methodologies. Given what was applied to the members of the Municipal Music Band of Itirapina-SP, in the second half of 2019, based on the observations of what was proposed with what was done, it is possible to understand the learning process of those involved, according to their limitations.
The teaching of rhythm in the municipal band of Itirapina-SP: experience report
Keywords: Ensino de rítmica; Educação musical; Banda de música; Rhythmic teaching; Music education; Music band; LINGUISTICA, LETRAS E ARTES::ARTES::MUSICA